Sports in society issues and controversies - Coakley, Jay J. Ph. D. (McGraw-Hill LLC, 2021)
"For over 30 years, Sports in Society has been a resource in the cultural, interactional, and structural dimensions of sports. The Thirteenth Edition provides a thorough introduction to the sociology of sport by raising critical questions to explore the relationships between sports, culture, and society. This text takes an issues-oriented approach to the study of sports in society and encourages the discussion of current sports-related controversies" -- Provided by publisher